Current and future cholera vaccines. (29th February 2020) - Shaikh, Hanif; Lynch, Julia; Kim, Jerome; Excler, Jean-Louis
Abstract: Cholera remains a major global public health problem that is primarily linked to insufficient access to safe water and proper sanitation. Oral Cholera Vaccine (OCV) has been recommended as an additional public health tool along with WASH in cholera endemic countries and in areas at risk for outbreaks. The new generation OCV is safe and offers good protection in older children and adults while limited protection in younger children less than five years of age has been observed. The combination of direct vaccine protection and vaccine herd immunity effects makes OCV highly cost-effective and, therefore, attractive for use in developing countries. Additionally, in recent studies OCV was safe in pregnant women, supporting its use in pregnant women in cholera endemic countries. However, knowledge need to be developed for current vaccines for their prolonged duration of protection and vaccines need improvements for better immune response in younger children. A single dose vaccination regimen would be more cost-effective and easier to deliver. Recent approaches have focused on designing genetically attenuated cholera strains for use in single-dose cholera vaccines. The global demand for OCV has been boosted by the WHO recommendation to use OCV and is driven largely by epidemics and outbreaks and has been increasing due to the availability of cheaper easy-to-use vaccines, feasibility of mass OCV vaccination campaigns, demonstration of protection to underserved population in precarious situations, and vaccine costs being borne by Gavi (Vaccine Alliance). For rapid access in emergency and equitable distribution of OCV in cholera-endemic low-income countries, a global OCV stockpile was established in 2013 with support from the Global Alliance for Vaccines and Immunization. The three WHO-prequalified vaccines are Dukoral®, Shanchol™, Euvichol® (and Euvichol® Plus presentation), the latter two being included in the stockpile.